Relatioship of Some Biochemical Variance with Hepatitis Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Hepatitis is a viral disease; it has a wide distribution among peoples in different countries' and it has more than five common types named; A, B, C, D and E. The serum level of total protein, albumin and ferritin was estimated in patients with chronic hepatitis B and C, in male and female aged from 19 – 50 years; at the same time same variance was measured in apparently normal healthy volunteers. A patient with other liver disease was excluded from this search.      The average values for total protein, albumin,and ferritin for normal volunteers are (5.33, 4.724 and 51.485 g/ dl) respectively for male and 5.342, 4.733 and 51.667 g/ dl in thefemale. While its value in HBV was (3.399, 2.878 and 77.909 g/dl) for male and 3.429, 3.092 and 137.091g/dl in female respectively. While in HCV, the value for total protein, albumin and ferritin was (4.045, 3.462 and 151.182 g/dl) respectively in male and 3.838, 3.391 and 68.167 respectively in thefemale. Using statistical analysis, the results indicate that there is a significant value for all variances when compared with the control in both cases B and C. The p-value was highly significant its value in HBV male patients is 6.4E-19, 5.11E-17 and 1.96E-12 for total protein, albumin and ferritin respectively and 1.6E-18, 2.03E-15 and 3.65E-24 for female. While in type HCV male patients the p- values were 8.01E-10, 1.9E-10 and 5.13E-17 for total protein, albumin and ferritin respectively, in female the values are 1.79E-16, 3.36E-12 and 1.78E-05 respectively.The results indicate also a positive correlation between all of the variance in the two types of patients